2023
DOI: 10.1186/s13293-023-00524-9
|View full text |Cite
|
Sign up to set email alerts
|

Are we moving the dial? Canadian health research funding trends for women’s health, 2S/LGBTQ + health, sex, or gender considerations

Abstract: Background Sex and gender impacts health outcomes and disease risk throughout life. The health of women and members of the Two-Spirit, Lesbian, Gay, Bisexual, Transgender, Queer or Questioning (2S/LGBTQ +) community is often compromised as they experience delays in diagnosis. Distinct knowledge gaps in the health of these populations have prompted funding agencies to mandate incorporation of sex and gender into research. Sex- and gender-informed research perspectives and methodology increases r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…However, despite these well-established discrepancies, sex-stratified data from randomized clinical trials of AD treatments is scarce 46,47 . Even when considering pre-clinical models, the potential for sex differences is often not reported or assessed 48,49 . The results of the current study identify both a sex difference in the baseline expression density of PV-INs in female humans and mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these well-established discrepancies, sex-stratified data from randomized clinical trials of AD treatments is scarce 46,47 . Even when considering pre-clinical models, the potential for sex differences is often not reported or assessed 48,49 . The results of the current study identify both a sex difference in the baseline expression density of PV-INs in female humans and mice.…”
Section: Discussionmentioning
confidence: 99%
“…En la participación de las expertas de las áreas de salud ocupacional, administración y gestión, violencia en el trabajo, y ambientes laborales, se observó diferencias en formación y área de desempeño actual lo que explica, en cierta medida, algunos focos diferenciados entre los grupos, como por ejemplo: la aplicación de perspectiva de género en la redacción de ítems por parte de expertas chilenas. La consideración de la perspectiva de género en todas las etapas de la investigación científica ha cobrado fuerza, al punto de convertirse en una política en ciertos países desarrollados (19) . De esta forma, las observaciones entregadas por dichas expertas se encontrarían alineadas con las guías internacionales actuales.…”
Section: Discussionunclassified
“…Corresponde a la calidad de vida profesional percibida por una persona que provee de ayuda, lo anterior incluye aspectos positivos como negativos de hacer el trabajo que influyen en la calidad de vida profesional (18,19) .…”
Section: Calidad De Vida Profesionalunclassified
“…In a previous study, we examined the published public abstracts of all Operating and Project Grants funded by CIHR from 2009 to 2020 using the CIHR Funding Decisions Database (see Stranges et al, 2023 for detailed methodology). Operating and Project Grants are CIHR's major funding competitions (akin to R01 mechanisms through the NIH).…”
Section: Methodsmentioning
confidence: 99%
“…Given the importance of studying 2S/LGBTQ+ health questions, it is concerning that recent research from our group revealed that less than 1% of all the Canadian Institutes of Health Research (CIHR) Operating and Project Grants were awarded to projects considering 2S/LGBTQ+ health from 2009-2020 21 . This finding highlights that 2S/LGBTQ+ health requires explicit attention and funding dollars to address the long-standing social and health disparities within these populations.…”
Section: Introductionmentioning
confidence: 99%